Research governance in placebo-controlled trials: Is the EMA/ICH position consistent in itself and in accordance with the declaration of Helsinki?. (September 2014) - Lenk, Christian; Hoppe, Nils
The European Medicines Agency and the International Conference on Harmonisation of Technical Requirements for Registration of Pharmaceuticals for Human Use are powerful international institutions for the regulation of biomedical research. Although not directly concerned with the ethical aspects of research, both institutions have disseminated position papers on ethical issues relating to the use of placebos in clinical trials. What appears initially to be guidance on the methodology of placebo-controlled trials (with very technical content) clearly has some far-reaching implications for the extent of risk patients can be expected to be subjected to in such trials. On the basis of this guidance, this article questions how much additional harm to patients would be acceptable in placebo-controlled trials in comparison with active-control trials. The article will show that the instruments provided in the guidance are unsuitable, remaining unclear on vital points and thereby leaving patients, researchers and research ethics committees without appropriate direction. In conclusion, placebo-controlled trials urgently need more appropriate regulation to ascertain an acceptable level of risk for participating patients in relation to additional harm.